The transition home of extremely premature babies: An integrative review. Issue 1 (February 2021) - Green, Janet; Fowler, Cathrine; Petty, Julia; Whiting, Lisa
Abstract: Taking a premature baby home after an often-protracted period on the neonatal unit can be stressful for parents and they are often confronted with an unexpected reality. The transition to motherhood and parenthood has occurred in the neonatal unit, under the watchful eye of neonatal nurses. When the baby goes home, parents are expected to take on the full-time caregiving role of a baby who may require around the clock care with medications, home oxygen, feeding issues and monitoring. The level of preparation for the transition home of the premature baby can impact on how the family survives and thrives. It is not surprising that parents may find this challenging because the growth and development trajectory of extremely premature babies can be markedly different from a term infant requiring tailored support. This article is an integrative review of the literature focusing on parents' experience of transitioning home from a neonatal unit with a premature baby. Six themes were identified, and an analysis is presented: namely, transition, unique needs of premature babies, discharge preparation and readiness, discharge learning content, maternal mental health and the role of the neonatal nurse in transition.